Passive Acoustic Source Tracking Using Underwater Distributed Sensors - Seung-Yong Chun; Ki-Man Kim (International Journal of Distributed Sensor Networks)
Passive acoustic source tracking using underwater distributed sensors has been a severe problem because of the complexity of the underwater channel and the limited resources of the sensors. In this paper, we propose an acoustic source tracking algorithm using underwater distributed sensors. According to the waveguide invariant theory, a slope of the interference pattern which is seen in a spectrogram is proportional to range of the acoustic source. The proposed algorithm matches the interference patterns at the distributed sensors and calculates a distance ratio between source and sensors. A locus of the source by the principal of the circle of Apollonius is estimated. The Apollonius circle, however, still keeps the ambiguity against the correct source location. In addition hyperbola equation is introduced into localization algorithm by estimating time difference of arrival between the received signals at the distributed sensors. Finally the cross point of the circle and hyperbola can be estimated as the position of the acoustic source. The proposed algorithm is tested on sea trial data for acoustic source ranges of 400–2,000 m and frequencies from 50 to 750 Hz. The results show that the proposed algorithm successfully estimates the source location within an error bound of 7.3%.